Covid-19 Responsive Public Space Signage Design for Children from Physical Distancing Aspects at Lapangan Merdeka, Pematangsiantar - Pasaribu, Nanda Rosaline; Ristianti, Novia Sari (Universitas Negeri Semarang, 2022)
Abstract. Adaptation of public space users requires COVID 19 responsive design elements to support public health, especially for children aged 7-12 years who are classified as vulnerable and still need public space to play and socialize. The Lapangan Merdeka area is a public open space where children make up about 60% of visitors. Currently, there is still negligence in the application of health protocols. This study considers design requirements in implementing physical distancing, such as signage aspects. The quantitative method is used in this research. The analysis stages consisted of identifying the child's characteristics through behavior-setting and place-setting; and formulating design element needs through signage aspects such as directional signage, informative signage, and identification signage. The research result shows three-element of signage. First is directional signage, such as a circulation regulation on the surfaces of the jogging track. It is used for the signing facility on the jogging track. It uses a board stuck in the ground and is placed in the area leading to the field, and uses an information board with 1-1.5 meters on the jogging track. Second, informative signage such as an x-banner at all facility points. Third, identification signage such as a board containing an area plan and placed near the words